La gerencia administrativa de Federación Deportiva Provincial de Zamora Chinchipe en la disciplina de boxeo y su incidencia en los resultados competitivos de los boxeadores seleccionados en el periodo 2007-2013 - Soto Celi, Tairon Fabian (2014)
As a student of physical culture of the National University of Loja, make the present thesis project at facilities of Sports Federation provincial de Zamora Chinchipe. To check if it has an efficient administrative management to optimize the competitive results of selected boxers, by deriving the following item: ¨the administrative management of Sports Federation provincial de Zamora Chinchipe in the discipline of boxing and its impact on competitive outcomes of the boxers selected for the period 2007-2013¨ proposed alternative, with which I have realized that there is a proper argument about poor competitive performance of the discipline of boxing and as such within the administrative framework of the management system I believed should be the study of the following problem: ´´como affects the administrative management of Sports Federation provincial de Zamora Chinchipe in the discipline of boxing in the competitive results of selected boxers in the period 2007 - 2013 ", from which are derived the following objectives: General objective: determine if Zamora Chinchipe Provincial Sport Federation has a good administrative management in the discipline of boxing that optimize the competitive results of the boxers selected for the period 2007-2013, objectives specific: Analyze whether or not the argument that uses the administrative management of the discipline of boxing to improve competitive performance of the boxers selected by Provincial Sport Federation is correct and check if the attitude of administrative management is optimal for the development of competitive results of the boxers selected by province of Zamora Chinchipe Sports Federation I have also continued with the review of literature which is comprised of the following points.-administrative management, sports management, conceptualization of boxing and history and competitive results. Within this research work I have used the following methods that are: the method of inductive, deductive method, Analytical method and scientific method, which have helped me to get results based on surveys to coaches and athletes of Sports Federation provincial de Zamora Chinchipe; same results I have proceeded to make the argument that is based on the responses from the surveys applied where taking into account three aspects q are the analysis, interpretation and decision and also reaching the conclusions and recommendations.